My Obscure Career as an Aspiring Poet. Issue 1 (2nd January 2021) - Stelzig, Eugene
ABSTRACT: 'My Obscure Career as an Aspiring Poet' is an account of my struggle and endless frustration, since my undergraduate days at the University of Pennsylvania, to get my poetry published. That struggle has been ongoing for nearly six decades now, with only some few and very intermittent successes.